Long noncoding RNA, PURPL is associated with aneuploidy and its magnitude of expression level is dependent on P53 status - Malakar, Pushkar (Frontiers in Cell and Developmental Biology, 2024)
Long non-coding RNAs (lncRNAs) are a fascinating, but still largely uncharacterized, class of genes. Recently, lncRNAs have attracted significant attention due to their emerging functions in development and disease. The role of lncRNAs in chromosome instability or aneuploidy is not extensively studied. We started with the objective of characterizing lncRNAs that play an important role in chromosome instability (CIN) or aneuploidy. Studies have demonstrated that CIN, or aneuploidy, controls the tumor microenvironment and stimulates inflammatory signaling. Here, we report the initial functional characterization of PURPL in the context of chromosomal instability or aneuploidy. We report the expression of lncRNA PURPL in three experimental models of chromosomal instability, or aneuploidy. In addition, the study also showed that the extent or magnitude of PURPL expression is dependent upon p53 status. Our research also showed that turning off PURPL is enough to create a CIN phenotype in RPE-1 cell lines that were previously karyotypically stable. Moreover, PURPL knockdown cells are more sensitive to CIN or aneuploidy inducers. This shows PURPL is essential for maintaining chromosomal or genomic stability in mammalian cells. Collectively, the study demonstrated that lncRNA-PURPL significantly contributes to CIN, or aneuploidy.